2019
DOI: 10.1136/neurintsurg-2019-014962
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endoscopic evacuation, stereotactic aspiration, and craniotomy for treatment of basal ganglia hemorrhage

Abstract: BackgroundThe main surgical techniques for spontaneous basal ganglia hemorrhage include stereotactic aspiration, endoscopic aspiration, and craniotomy. However, credible evidence is still needed to validate the effect of these techniques.ObjectiveTo explore the long-term outcomes of the three surgical techniques in the treatment of spontaneous basal ganglia hemorrhage.MethodsFive hundred and sixteen patients with spontaneous basal ganglia hemorrhage who received stereotactic aspiration, endoscopic aspiration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 28 publications
0
31
1
2
Order By: Relevance
“…Only 24.65 and 20% of patients have an initiate GCS score ≤ 8 in the STICH study and MISTIE study. Whereas, 59% of patients have an initiate GCS score ≤ 8 in our center (23).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Only 24.65 and 20% of patients have an initiate GCS score ≤ 8 in the STICH study and MISTIE study. Whereas, 59% of patients have an initiate GCS score ≤ 8 in our center (23).…”
Section: Discussionmentioning
confidence: 68%
“…Besides, our previous study compared the long-term outcomes of the three surgical techniques in the treatment of spontaneous basal ganglia hemorrhage. According to the subgroup analysis stratified by hematoma volume, endoscopic aspiration can decrease the 6-months mortality of spontaneous basal ganglia hemorrhage, especially in patients with a hematoma volume ≥ 40 ml ( 23 ). Thus, the present study explored the long-term outcomes of endoscopic evacuation, stereotactic aspiration, and craniotomy in the treatment of large basal ganglia hematoma patients (≥40 ml) with initial GCS ≤ 8.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that compared with MIC evacuation, endoscopic evacuation could significantly decrease 6-month mortality in patients with basal ganglia hemorrhage [ 20 ]. However, among the surviving patients, only 22.4% achieved a good neurological recovery (mRS score ≤ 2) at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Besides STICH trials, there are many reported RCTs including the National Institutes of Health spon-sored Minimally Invasive Surgery Plus recombinant tissue plasminogen activator (rt-PA) for ICH Evacuation (MISTIE) trial evaluating stereotactic thrombolysis, the endoscopic arm of MISTIE referred to as the Intraoperative Stereotactic Computed Tomography-Guided Endoscopic Surgery trial, the Early Minimally-Invasive Removal of Intracerebral Hemorrhage trial and the Minimally Invasive Endoscopic Surgical Treatment With Apollo/ Artemis in Patients With Brain Hemorrhage [14]. Although most recently reported MISTIE III trial concluded that MISTIE did not improve the proportion of patients who achieved a good response 365 days after ICH [15], many other studies including meta-analysis reported that the minimally invasive procedures especially for endoscopic evacuation, seem to be more effective than conservative treatment in reducing both morbidity and mortality [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%